The Role of Social Capital in Clove Marketing: A Case Study of Rural South Sulawesi - Jumiati Jumiati; Nadir Nadir; Ardi Rumallang; Ikmal Saleh; Saleh Molla; Akbar Akbar; ika Fitri (Jurnal Ilmu Pertanian Indonesia, 2026)
The purpose of this research was to examine clove marketing channels and the impact of social capital in facilitating marketing processes in Gowa Regency, South Sulawesi. In-depth interviews were conducted with clove producers, intermediate traders, and wholesalers to obtain data for a qualitative case study. The data was evaluated thematically to identify patterns of trust, reciprocity, and network interaction in the clove marketing system. The findings revealed two major marketing channels: (1) farmers sell wet cloves to intermediary traders, who then distribute the product to wholesalers and industries, and (2) farmers sell dried cloves directly to wholesalers for higher pricing and greater market control. Trust, reciprocal relationships, and adherence to social standards facilitate unsecured capital loans, promote information exchange, and assure compliance with informal agreements. Strong community values, particularly gotong royong (mutual cooperation) and solidarity, enhance the robustness and adaptation of clove marketing systems. The combination of social capital and digital networking enhances access to market knowledge and promotes sustainable marketing practices. The findings highlight the necessity of increasing social capital to improve farmer welfare, increase market efficiency, and create a sustainable marketing framework. Keywords: clove, marketing channels, rural agribusiness, social capital, trust